Effect of nursing method and stocking density on the performance of early weaned rabbits - Rashwan, A. A.; Matics, Zsolt; Szendrő, Zsolt; Orova, Zoltán; Biróné Németh, Edit; Radnai, István (Acta Agraria Kaposváriensis, 2007)
The aim of the study was to compare the traditional rearing method with a two-phase method, with higher stocking density at early age, on productive traits of growing rabbits depending on their milk supply until weaning at 21 days of age. 252 rabbits were nursed by one or two does. Both groups were divided into two subgroups. In the first, 3 rabbits per cage were kept between 21 and 70 days of age (Group 3/3). In the other group 6 rabbits were kept between 21 and 42 days of age and later only 3/cages were reared till 70 days of age (Group 6/3). The effect of number of nursing does was significant on the feed intake (85 or 81 g/days; P < 0.05) and on the weight at 70 days of age (2093 or 2005 g; P < 0.05) for rabbits nursed by 2 or 1 does, respectively. It was an important observation that the kits nursed by two does and reared 6/cage are able to reach the nipple drinkers more easily than that of nursed by one doe and reared on a lower density (3 kits/cage) during the first week after weaning. This was the reason for the significant difference in weight gain after weaning. But the rearing method has no effect on the overall weight gain between the age of 21 and 70 days, on the body weight, feed intake and feed conversion. The effect of stocking density was significant on kit mortality between days 21 and 70; its value was 36 and 18% for the group 3/3 and group 6/3, respectively. Rearing the rabbits in two phases, 6 rabbits/cage between 21–42 days and 3 kits/cage between 42–70 days of age was found to be economically advantageous since more rabbits were housed in a cage or in a building matched with lower mortality and without any negative influence on the other traits.